1998
DOI: 10.1523/jneurosci.18-01-00419.1998
|View full text |Cite
|
Sign up to set email alerts
|

Brain Dopamine Neurotoxicity in Baboons Treated with Doses of Methamphetamine Comparable to Those Recreationally Abused by Humans: Evidence from [11C]WIN-35,428 Positron Emission Tomography Studies and DirectIn VitroDeterminations

Abstract: The present study sought to determine whether doses of methamphetamine in the range of those used recreationally by humans produce brain dopamine (DA) neurotoxicity in baboons and to ascertain whether positron emission tomography (PET) imaging with the DA transporter (DAT) ligand [11C]WIN-35,428 ([11C]2beta-carbomethoxy-3beta-(4-fluorophenyl)-tropane) could be used to detect methamphetamine-induced DAT loss in living primates. Baboons were treated with saline (n = 3) or one of three doses of methamphetamine [0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

16
133
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 202 publications
(149 citation statements)
references
References 54 publications
16
133
0
Order By: Relevance
“…1-Methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP) is a neurotoxin that induces parkinsonism in both humans [4] and non-human primates [5] with the cognitive, biochemical, histological and classical behavioral changes that occur in PD [6] . Therefore, Increasing evidence has suggested that single photon emission computed tomography (SPECT) and positron emission tomography (PET) imaging can be used to sensitively and objectively evaluate the integrity of the nigrostriatal dopaminergic system and may be useful tools for providing diagnostic information on PD [7][8][9][10] . There are numerous SPECT and PET imaging tracers for monitoring the integrity of dopaminergic neurons.…”
Section: Introductionmentioning
confidence: 99%
“…1-Methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP) is a neurotoxin that induces parkinsonism in both humans [4] and non-human primates [5] with the cognitive, biochemical, histological and classical behavioral changes that occur in PD [6] . Therefore, Increasing evidence has suggested that single photon emission computed tomography (SPECT) and positron emission tomography (PET) imaging can be used to sensitively and objectively evaluate the integrity of the nigrostriatal dopaminergic system and may be useful tools for providing diagnostic information on PD [7][8][9][10] . There are numerous SPECT and PET imaging tracers for monitoring the integrity of dopaminergic neurons.…”
Section: Introductionmentioning
confidence: 99%
“…To date, most studies involving METH administration and the consequent CNS pathology have focused on neurotoxicity in the striatal dopamine projections (Ricaurte et al, 1984;Cadet et al, 1998;Villemagne et al, 1998;Harvey et al, 2000b). However, the applicability of these studies to human METH abuse has been questioned due to differences between the pattern of drug-abuse dosage/frequency in human users and those used in animal studies.…”
Section: Introductionmentioning
confidence: 99%
“…In rodents, one of the most common acute high dose METH administration protocols used is 10 mg/kg injected four to five times over the course of a single day at 2 h intervals (Broening et al, 1997;Chapman et al, 2001;Gluck et al, 2001), although doses as high as 40 mg/kg are also administered (Sabol et al, 2001). Short-term protocols are often utilized as well in nonhuman primate studies, with METH doses ranging from 0.5 to 2 mg/kg given for just 1-5 days, two to four times each day (Melega et al, 1997;Villemagne et al, 1998;Harvey et al, 2000a, b). However, such dosing can lead to severe symptoms of METH toxicity resulting in the stoppage of the scheduled dosing regimen or even death of experimental animals.…”
Section: Introductionmentioning
confidence: 99%
“…In the PET study with [ 18 F] FCT in the cocaine self-administration model with monkeys, the laterality of DAT function was changed even before enough cocaine was consumed to produce significant overall changes in receptor and transporter availability [58] . has also revealed a reduction of the DAT in MA abusers and in baboons after MA injection [63][64][65][66] .Methylphenidate ( d-threo-MP to the DAT, suggesting that it is a useful PET tracer for imaging presynaptic dopaminergic neurons [67] . A PET imaging study using pretreatment with MP showed a marked decrease of [ 11 C] d-threo-MP binding in the human brain [68] .…”
mentioning
confidence: 99%